Disentangling the role of light and nutrient limitation on bacterivory by mixotrophic nanoflagellates - DeVaul Princiotta, Sarah (2023)
Many phytoplankton taxa function on multiple trophic levels by combining photosynthesis and ingestion of bacteria, termed mixotrophy. Despite the recognition of mixotrophy as a universal functional trait, we have yet to fully resolve how environmental conditions influence community grazing rates in situ. A microcosm study was used to assess bacterivory by mixotrophic nanoflagellates following nutrient enrichment and light attenuation in a temperate lake. We found contrasting results based on assessment of mixotroph abundance or bacterivory. Despite an interactive effect of nutrient enrichment and light attenuation on mixotroph abundance, significant differences within light treatments were observed only after enrichment with P or N+P. The greatest abundance of mixotrophs across treatments occurred under co-nutrient enrichment with full exposure to irradiance. However, bacterivory by mixotrophic nanoflagellates was greatest under shaded conditions after either N or P enrichment. We suggest that PAR availability dampened the stimulatory effect of nutrient limitation, and bacterivory supplemented a suboptimal photosynthetic environment. In a saturating light regime, the mixotrophic community was less driven to ingest bacteria because photosynthesis was able to satisfy energetic demands. These findings quantify community bacterivory in response to environmental drivers that may characterize future ecosystem conditions and highlight the importance of considering grazing rates in conjunction with abundance of mixotrophic protists.